Identification of physical and chemical factors regulating gene expression and infectivity of the Lyme disease spirochetes - Pavlasová, Veronika (Jihočeská univerzita, 2022)
Borrelia afzelii is one of the main Lyme disease causative agents. It is known that differential gene expression during the Borrelia life cycle can relate to infectivity for mammals, including humans. However, just a little is known about what affects these changes in expression. Here, we investigate the effect of temperature and common blood nutrients on Borrelia afzelii differential gene expression and transmission efficiency while stimulating the ticks with chosen substances.
Identification of physical and chemical factors regulating gene expression and infectivity of the Lyme disease spirochetes
Keywords: Borrelia; Ixodes; ticks; Lyme disease; gene expression; ospA; ospC; bbk32; amino acids; sugars; qPCR; qRT-PCR